In Vivo Conversion of the Single-Stranded DNA of the Kilham Rat Virus to a Double-Stranded Form - Salzman, Lois Ann (1973)
Kilham rat virus (KRV) contains linear, single-stranded DNA in the virion. The fate of radioactive viral DNA was followed after infection of monolayer cells. Within 60 min after infection of cells, 28 to 42% of the parental viral DNA is converted to a new form. This new DNA form is believed to be double stranded and linear on the basis of its sedimentation in neutral and alkaline sucrose gradients, elution from hydroxyapatite columns, its buoyant density in equilibrium CsCl density gradients, and appearance in the electron microscope. The double-stranded linear KRV DNA may be analogous to the replicative form of certain bacteriophages, including φX174, which contain single-stranded circular genomes.